Acyclovir-Induced Nephrotoxicity: The Protective Benefit of Curcumin - Elias Adikwu; James Kemelayefa (European Journal of Biology)
Objective: Nephrotoxicity may decrease the clinical use of acyclovir (ACV). Curcumin (CUM) is used traditionally as treatments for some diseases. This study examined the protective effect of CUM against ACV-induced nephrotoxicity in rats. Materials and Methods: Forty-five male Wistar rats (240–250g) randomized into nine groups (n=5) were used. Group 1(Placebo control) received water (0.2mL/day) intraperitoneally (i.p) whereas group 2 (Solvent control) received corn oil (0.2mL/day) per oral (p.o) for 7 days. Groups 3-5 received CUM (25, 50 and 100 mg/kg/day p.o) for 7 days. Group 6 received ACV (150 mg/kg/day i.p) for 7 days. Groups 7-9 were pre-treated with CUM (25, 50 and 100 mg/kg/day p.o) before the treatment with ACV (150 mg/kg/day i.p) for 7 days. On day 8, the rats were anesthetized; blood samples were collected and evaluated for serum biochemical indices. The k idneys were weighed and assessed for histology and oxidative stress indices. Results: ACV produced no significant (p>0.05) effects on the body and kidney weights of rats when compared to control. ACV caused significant (p<0.001) elevations in serum creatinine, urea, uric acid and kidney malondialdehyde levels when compared to control. ACV significantly (p<0.001) decreased kidney glutathione,catalase, glutathione peroxidase, superoxide dismutase, serum total protein, albumin, potassium, chloride, sodium and bicarbonate levels when compared to control. Tubular necrosis and hypercellular glomerulus with mesangial proliferation occurred in the ACV-treated rats. ACV-induced nephrotoxicity was abrogated in a dose-related fashion by CUM 25mg/kg (p<0.05), 50mg/kg (p<0.01) and 100mg/kg (p<0.001) when compared to ACV. Conclusion: CUM may clinically prevent ACV-induced nephrotoxicity.